Analisis Politomi Rasch Model Skala PTSD - Praekanata, I Wayan Indra; Suranata, Kadek; Gading, I Ketut; Lestari, Luh Putu Sri (Jurnal Konseling dan Pendidikan, 2024)
Post-Traumatic Stress Disorder (PTSD) is a significant mental health issue, particularly in Indonesia with its complex cultural diversity. This study aims to assess the validity of the Indonesian Version DSM-V PTSD scale using an Item Response Theory (IRT) approach through the Rasch model. The research method involved 70 respondents who experienced trauma, measured using a Likert scale consisting of 20 items. Data were collected from an online questionnaire and analysed using the Rasch Polytomous model. The results indicate that the PTSD scale has good reliability, with a Person Reliability value of 0.865. The analysis revealed that several items have varying difficulty levels, suggesting the need for adjustments to reflect local experiences. The Partial Credit Model (PCM) was found to be more suitable than the Rating Scale Model (RSM), with likelihood ratio test results showing significant differences (χ² = 155, p < .001). This study provides new insights into the importance of validating psychological measurement tools in diverse cultural contexts and contributes to the development of better mental health policies in Indonesia.